Calcareous nannofossil stratigraphy of the Upper Cretaceous–lower Paleocene sequence from the Dokan section, Sulaimani, Kurdistan- Iraq - Kharajiany, Soran O. A.; Sherwood W. Wise, Jr.; Al-Qayim, Basim A. (Sulaimani Journal for Pure and Applied Sciences, 2018)
The boundary of the Cretaceous/Tertiary in the Kurdistan region of Iraq is still under debate. Most previous studies consider the Danian sediments to be absent. This paper examines the boundary in the Dokan area northwest of the Sulaimani city of Kurdistan in northern Iraq. This research analyzes calcareous nannofossil assemblages and the biostratigraphy of the boundary. The sequence in the study section is characterized by alternations of olive green to greenish gray sandstone, siltstone, shale and marlstone of the Tanjero Formation of the late Campanian- Maastrichtian and the overlying Kolosh Formation of the early Paleocene. The upper part of the section includes thick sandstone beds and a reworked bioclastic conglomerate bed in addition to a dark- grey, silty calcareous shale. The study shows that deposition across the boundary is continuous. The boundary is biostratigraphically delineated by the last occurrence of Maastrichtian taxon and the first occurrences of Biantholithus sparsus, Cruciplacolithus spp. and Coccolithus pelagicus of biozone NP1, which indicate no hiatus. This succession highlights the occurrence of the early Danian sequence at the bottom of the Kolosh Formation.
Keywords: Dokan; KT boundary; early Danian; NP1; Biantholithus sparsus; Tanjero; Kolosh; Sulaimani; KurdistanIraq